THE CURRENT STATE OF TRAINING FUTURE SOCIAL EDUCATORS TO WORK WITH VETERANS OF MILITARY SERVICE (Innovative professional education, 2025)
The publication substantiates the relevance of studying the readiness of social educators to support the adaptation of military service veterans in the context of the development of Ukraine’s vocational education system. It highlights contemporary challenges caused by the significant increase in the number of servicemen returning to civilian life. The paper analyzes directions for improving the content of professional training for future social educators, particularly through the implementation of competency-based, interactive, and psychological-rehabilitation teaching methods. The necessity of a comprehensive approach to student training and volunteer practice, as well as the modernization of educational programs and regulatory frameworks, is outlined to ensure effective support for veterans and their families
Keywords: social educators, readiness for veterans’ adaptation, vocational education, psychosocial support